Ecological Assessment of the Plant Communities inside Kangla Fort, Manipur - Singh2, N. Beenakumari Devi1 and N. Sanjoy (Journal of Experimental Sciences, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The ecological assessment of the plant communities inside Kangla Fort, an ancient historical site in Manipur (240 N latitudes and 940 E longitudes) have been carried out with details of the floristic study i.e. habitat, heights, and natures of the perennating buds together with the seasonal changes in the diversity of the plant species during the period of one year at monthly intervals. For the present study, two study sites were selected inside Kangla viz. Site I (protected, by barb-wire fencing, from grazing and other biotic influences), and Site II (unprotected area exposed to grazing and other biotic influences). Altogether 54 plant species belonging to 24 families were recorded from the grassland communities in the two study sites. Out of the 54 plant species, maximum number of 33 species belonged to Therophytes (61.11%), 9 species to Hemicryptophytes (16.67%), and 8 species to Geophytes (14.81%). Chamaephytes were represented by only 4 species (7.41%) while Phenerophytes were absent. As the present study showed the predominance of therophytes and geophytes over other life forms, the study site could be categorised as a Thero-geophytic phytoclimate indicating a hot and humid climate.